The Reversal of the Exemplifying Role of History in Horace Walpole s “The Castle of Otranto ” - Barć, Sybilla (Stylistyka, 2021)
According to the traditional understanding, the role of history in literary works was te- aching by example. History was expected to provide readers with ready formulae for appropriate behaviour, to introduce models to follow and to identify with, as well as to explain the difficulties of life. In the second half of the eighteenth century such an appro- ach to history tumed out to be inadeąuate. This article presents Horace Walpole’s The Castle of Otranto - the first Gothic novel in English literaturę - as a work that subverts exemplary historicism by reversing the traditional exemplifying role of history. Published in 1764, when neoclassical ideals were still being promoted by such important writers as Doctor Samuel Johnson, Walpole’s novel commenced a new trend in literaturę that fully developed in Romanticism proper. It is not really intended to teach by example or to ren- der medieval history in terms of modem Enlightenment standards. Instead of rational explanations and balanced opinions its readers get an abundance of supematural pheno- mena and extravagant events. With its emphasis on entertainment rather than education, the story is a signum temporis, a significant step on the way towards the priority of aesthe- tic values in literary works. The article focuses on the novel in the context of its publica- tion in the Age of Reason. The two different prefaces are briefly analysed, and the chan- ging critical reception is presented. Some attention is also given to Clara Reeve’s The Old English Baron as an immediate successor of Walpole’s book, and simultaneously a strong criticism of his innovative perception of the role of literaturę. Despite the multitude of un- favourable comments by eighteenth-century writers and critics, the conclusion reached in this article is that such Gothic novels opened up a new perspective in the literary world. Walpole’s role as the forerunner in this field remains unquestionable.